Citizen Participation in Child Protection as an Effort to Prevent Violence against Children in Tasikmalaya Regency - Kurniawan, Kukun; Affandi, Ideus; Anggraeni, Leni (Angstrom Centre of Education, 2023)
As one of the human resources, children need guidance and a sense of security to ensure that the child's physical, spiritual and social growth as a whole is balanced and harmonious. To enforce this rule, the government enacted Law Number 23 of 2002 concerning Child Protection, some of the provisions of which were amended by Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. the presence of the State in protecting children certainly requires the participation of citizens in implementing the Child Protection Law as is the case with one of the districts that has formed the Regional Child Protection Commission (KPAD) in 2017, namely Tasikmalaya Regency. The role of the Regional Child Protection Commission (KPAD) is a form of participation forum for citizens as a preventive form of acts of violence against children which so far seems to be mushrooming in every room. The role of KPAD is very important to protect children's rights, guide, provide a sense of comfort and can reduce the number of violations of violence against children.